MODEL COOPERATIVE LEARNING DALAM MENANAMKAN NILAI AGAMA DAN BUDI PEKERTI PADA ANAK USIA DINI DI TK SURYA GEMILANG - Suhari; Adjie; Nashrul; Habib; Romlah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The instilling of religious values and moral character in early childhood is an important foundation in character formation that will influence children's development at the next level of education. One learning model that can support this process is Cooperative Learning, as it provides children with opportunities to learn through collaboration, social interaction, and direct learning experiences. This study aims to describe the planning and implementation of the Cooperative Learning model in instilling religious values and moral character in early childhood at TK Surya Gemilang, Malang City. The study used a qualitative approach with a descriptive research design. The research subjects consisted of the school principal, one teacher, and three students. Data were collected through observation, semi-structured interviews, and documentation. The validity of the data was established using source triangulation and technique triangulation, while data analysis referred to the Miles, Huberman, and Saldaña model, which includes data condensation, data display, and conclusion drawing. The results showed that learning planning had been systematically arranged through the preparation of Daily Lesson Plans (RPPH) that integrated the Cooperative Learning model, learning objectives, religious materials, learning media, the formation of heterogeneous groups, and the assessment of students' development. The implementation of learning took place through group activities combined with habituation practices such as reciting prayers, congregational prayers, memorizing short surahs, reading the Qur'an or Iqra', as well as various collaborative activities capable of developing attitudes of cooperation, responsibility, discipline, care, tolerance, and politeness. This study concludes that the Cooperative Learning model is effective in supporting the instilling of religious values and moral character in early childhood through learning that is active, collaborative, and aligned with children's developmental characteristics.